STUDY OF FRAUD TENDENCY: THE ROLE OF UNETHICAL BEHAVIORS AS MEDIATION - Hamidah, Siti; Reskino, Reskino (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2021)
Islamic banking and Islamic insurance are institutions that are trusted by the public that play an important role in the economy that should uphold Islamic values. But in fact, there are still many cases of fraud that occur in Islamic banking and Islamic insurance. This study aims to examine the determinant factor fraud tendency with the role of unethical behavior as mediation. The sample used is the financial staff of Islamic banking and Islamic insurance in DKI Jakarta as many as 118 respondents. The data analysis method used in this research is Partial Least Square (PLS-SEM). The results of this study indicate that the implementation of good corporate governance (GCG) practice has a significant effect on unethical behavior, but conformity compensation does not have a significant effect on unethical behavior. Conformity compensation, implementation of GCG practice, and unethical behavior has a significant effect on the fraud tendency. Furthermore, the implementation of GCG practice has a significant effect on fraud tendency through unethical behavior, but conformity compensation has no significant effect on fraud tendency through unethical behavior.